Pengembangan Potensi Pariwisata dalam Perspektif Reinventing Government (Studi di Dinas Kebudayaan dan Pariwisata Kabupaten Lamongan) - Ismuhadi Heru Wijayanto (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2013)
Abstract. Tourism Potensial Development in Reinventing Government Perspective. Lamongan Regency tourism have significant improvement in one last decade especially after built Lamongan Marine Tourism (WBL). This phenomena in tourism sector interested to examines in reinventing government perspective. This perspective is considered the most synchronous bureaucracy as an instrument to develop the tourism industry. This is because tourism is very close to how the government in order to understand the mechanism of enterprenuer public sector so it can be attractive to many visitors. The main idea of this concept is how entrepreneurial public sector bureaucracy in order to run the organization more competitive, effective and efficient through 10 principles ofÂ reinventing government. This research used qualitative approach with exploratory method in Disbudpar Lamongan Regency. data analysis by Miles and Huberman, it is concluded that the correspondence between the implementation of Reinventing Government perspective on the performance of the Department of Culture and Tourism Lamongan is achieving 80% compliance rate. This rate is obtained from the results of the 10 principles contained in the Reinventing Government, Disbudpar Lamongan meet 8 principles, while two other principles less fulfilling. keyword: Development, Tourism Potential, Reinventing Government. Â Abstrak : Pengembangan Potensi Pariwisata dalam Perspektif Reinventing Government. Pariwisata Kabupaten Lamongan mengalami kemajuan signifikan dalam satu dekade terakhir, terutama setelah dibangunnya Wisata Bahari Lamongan pada tahun 2004. Fenomena di sektor pariwisata ini menarik untuk dikaji dalam perspektif reinventing government. Perspektif ini dianggap paling sinkron sebagai instrumen birokrasi untuk mengembangkan industri pariwisata dikarenakan berhubungan erat dengan strategi wirausaha untuk menarik minat pengunjung. Gagasan utama dari konsep ini adalah bagaimana cara mewirausahakan birokrasi agar sektor publik dapat menjalankan roda organisasinya lebih kompetitif serta efektif dan efisien melalui 10 prinsip reinventing government. Penelitian ini menggunakan pendekatan kualitatif metode eksploratori dengan lokus Dinas Kebudayaan dan Pariwisata Kabupaten Lamongan. Berdasarkan dari hasil penelitian, diperoleh kesimpulan bahwa kesesuaian antara implementasi perspektif Reinventing Government terhadap kinerja Dinas Kebudayaan dan Pariwisata Kabupaten Lamongan adalah mencapai tingkat kesesuaian 80 %. Tingkat ini diperoleh dari hasil asumsi hitung 10 prinsip yang terdapat dalam Reinventing Government, Disbudpar Kabupaten Lamongan memenuhi 8 prinsip, sedangkan dua prinsip yang lainnya kurang memenuhi. kata kunci: Pengembangan, Potensi Pariwisata, Reinventing Government.